What influences adolescent girls’ decision-making regarding contraceptive methods use and childbearing? a qualitative exploratory study in Rangpur district, Bangladesh - Shahabuddin, A. S. M.; Nöstlinger, Christiana; Delvaux, Thérèse; Sarker, Malabika; Bardají, Azucena; Brouwere, Vincent De; Broerse, Jacqueline E. W. (© 2016 Plos One, 2018)
This article was published in the PLoS ONE[© 2016 PLoS ONE ] and the definite version is available at : https://doi.org/10.1371/journal.pone.0157664 . The Journal's website is at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0157664